SYSTEM FOR RECEIVING AND ISSUING MEMBERSHIP CARDS WINESA MUSIC STUDIO - Maman Syaifurahman (Jurnal Sistem Informasi, 1998)
technological advances that have been computerized work processes is expected to assist and speed up work processes and service receipts and issuance of membership cards WINESA MUSIC STUDIO, so hopefully the process of gathering data, preparing reports, and issuing a membership card can more quickly and efficiently.